Factors influencing secondary school students’ reading literacy: An analysis based on XGBoost and SHAP methods - Liu, Hao; Chen, Xi; Liu, Xiaoxiao (Frontiers in Psychology, 2022)
This paper constructs a predictive model of student reading literacy based on data from students who participated in the Program for International Student Assessment (PISA 2018) from four provinces/municipalities of China, i.e., Beijing, Shanghai, Jiangsu and Zhejiang. We calculated the contribution of influencing factors in the model by using XGBoost algorithm and SHAP values, and get the following findings: (1) Factors that have the greatest impact on students' reading literacy are from individual and family levels, with school-level factors taking a relative back seat. (2) The most important influencing factors at individual level are reading metacognition and reading interest. (3) The most important factors at family level are ESCS (index of economic, social and cultural status) and language environment, and dialect is negative for reading literacy, whereas proficiency in both a dialect and Mandarin plays a positive role. (4) Among the most important factors at school level are time dedicated to learning and class discipline, and we found that there is an optimal value for learning time, which suggests that reasonable learning time is beneficial, but overextended learning time may make academic performance worse instead of improving it.